2019
DOI: 10.1088/1674-1056/ab3f97
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sintering temperature on luminescence properties of borosilicate matrix blue–green emitting color conversion glass ceramics*

Abstract: The color conversion glass ceramics which were made of borosilicate matrix co-doped (SrBaSm)Si2O2N2: (Eu3+Ce3+) blue–green phosphors were prepared by two-step method in co-sintering. The change in luminescence properties and the drift of chromaticity coordinates (CIE) of the (SrBaSm)Si2O2N2: (Eu3+Ce3+) blue–green phosphors and the color conversion glass ceramics were studied in the sintering temperature range from 600 °C to 800 °C. The luminous intensity and internal quantum yield (QY) of the blue–green phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Compared with similar LiLaSiO 4 phosphors, the emission intensity does not decrease significantly, indicating that the stability of glass ceramics is relatively outstanding. 20 According to the emission spectrum in Figure 12(A), the thermal quenching activation energy of the 0.3% Tb 3+doped glass ceramics can be calculated using formula (5). In formula ( 5 emission spectra corresponding to 298 K and different temperature respectively.…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…Compared with similar LiLaSiO 4 phosphors, the emission intensity does not decrease significantly, indicating that the stability of glass ceramics is relatively outstanding. 20 According to the emission spectrum in Figure 12(A), the thermal quenching activation energy of the 0.3% Tb 3+doped glass ceramics can be calculated using formula (5). In formula ( 5 emission spectra corresponding to 298 K and different temperature respectively.…”
Section: F I G U R Ementioning
confidence: 99%
“…4 The current commercial generation of green light is obtained by using diverse laser light wavelengths to excite rare earth ions-doped phosphors. However, some defects of phosphors themselves restrict their application, such as poor water resistance, [5][6][7] opaqueness, 8,9 aging of the encapsulation material leading to a short life cycle and other shortcomings, 10 so there is an urgent demand for the development of a new light-emitting material that can overcome the aforementioned issues.…”
Section: Introductionmentioning
confidence: 99%
“…But a mono-element phosphorus featuring many emitting centers or redshifting rays is seen to be a good method for enhancing the efficiency of WLEDs. Codoping red-disputed lanthanide stimulators as Pr 3+ (611 nm, 1 D2 → 3 H4), Sm 3+ (616 nm, 4 G5/2 → 6 H7/2) and Eu 3+ (590 and nm, 5 D0 → 7 F1,2) or shifting of metallic particles like Cr 3+ (685 nm, 2 E → 4 A2) 10 and Mn 2+ (594 nm, 4 T1( 4 G) → 6 A1( 6 S)) via Mn 2+ -Si 4+ co-replacement for Y 3+ -Al 3+ (tetrahedral) was demonstrated to offer further red emissions within YAG:Ce 3+ [13], [14]. However, because of the low assimilation of particles from the blueemitted spectral region or ineffective energy conversion by Ce 3+ , the amplification of the red component is highly restricted in most of these circumstances.…”
Section: Introductionmentioning
confidence: 98%
“…MD simulations of metal-cluster collision, coalescence, and sintering reaction have been extensively performed. [1,[8][9][10][11][12][13][14][15][16][17] Marcelo et al reported core-shell (PtAu), alloyed (PdAu), and onion-like (CuAg) cluster structures by colliding two different metal clusters at various initial velocities. [3] Yang et al simulated the sintering reaction between Li and Pd metal clusters at different initial temperatures [8] and found that metal nan-oclusters may undergo structural transformation during collision and coalescence, [1,18,19] Grammatikopoulos et al conducted a classical MD simulation of palladium (Pd) clusters' coalescence and performed magnetron sputtering of inert gas for the condensation deposition of Pd nanoparticles.…”
Section: Introductionmentioning
confidence: 99%